Al-Islam wa-sa'ir al-adyan - al-Istanbuli, Husin Hilmi Ishiq Sa'id (Istanbul, Turkey : Hakikat Kitabevi, 2009)
This book deals with the fundamental principles of Islam, christianity, judaism, buddhism and brahmanism in a comparative way.
Keywords: Islam -- Relations